Integration of Google Earth Pro in Geographic Information System (GIS) Learning at SMKS Islam Pesantren Alam Indonesia - Uca, Uca; Mannan, Abdul; Tabbu, Muhammad Ansarullah S.; Amal, Amal (Yayasan Ahmar Cendekia Indonesia, 2024)
The rapid advancement of technology has significantly influenced education, including the integration of Geographic Information Systems (GIS) in geography lessons to prepare students for the demands of the digital era. This training was designed to enhance the understanding and skills of students at SMKS Islam Pesantren Alam Indonesia in Barru District in using Google Earth Pro for land mapping. The training was conducted through five stages: group approach, knowledge enhancement, spatial data creation, data processing, and evaluation. Results show that participants improved their understanding of GIS concepts and successfully applied practical skills, including spatial data interpretation and collection on a 5.23-hectare agricultural plot. The final evaluation indicated that participants were able to create accurate maps and databases of the agricultural area. Overall, this training effectively enhanced digital mapping skills among students and teachers, equipping them for technological challenges.